2000
DOI: 10.1038/sj.cdd.4400646
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induces caspase-independent retinal apoptosis in vitro

Abstract: Apoptosis is the mode of cell death in retinitis pigmentosa (RP), a heterogeneous group of retinal degenerations. The activation of the caspase proteases forms a pivotal step in the initiation and execution phase of apoptosis in many cells. Inhibition of caspases has been reported to prevent apoptosis in many model systems. However, we demonstrate the absence of caspase activation during retinal cell apoptosis in vitro which involves phosphatidylserine (PS) externalisation, DNA nicking and cell shrinkage. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
1
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 63 publications
6
76
1
1
Order By: Relevance
“…30,41 They represent an invaluable tool for the study of cone PCD, given the detection problems that can arise in studying dynamic events in cells that account for a mere 2.8% of total photoreceptors in the mouse retina. 28 In spite of the fact that previous studies in our group ruled out the involvement of caspases in several in vitro and in vivo models of photoreceptor degeneration, [42][43][44] (data not shown) and -12 were active during apoptosis of 661W cells. This conflicting data can readily be explained if one considers the differences between the models employed.…”
Section: Discussionmentioning
confidence: 57%
“…30,41 They represent an invaluable tool for the study of cone PCD, given the detection problems that can arise in studying dynamic events in cells that account for a mere 2.8% of total photoreceptors in the mouse retina. 28 In spite of the fact that previous studies in our group ruled out the involvement of caspases in several in vitro and in vivo models of photoreceptor degeneration, [42][43][44] (data not shown) and -12 were active during apoptosis of 661W cells. This conflicting data can readily be explained if one considers the differences between the models employed.…”
Section: Discussionmentioning
confidence: 57%
“…Caspase-independent apoptosis has also been observed in neuronal cells in response to ␤-amyloid, nitric oxide, and traumatic brain injury (Okuno et al, 1998;Selznick et al, 2000;Zhang et al, 2002) and in the models of photoreceptor cell death both in vivo (Carmody and Cotter, 2000) and in vitro (Donovan and Cotter, 2002). Previous studies showed that TMS increases DNA cleavage by S1 nuclease at both loop regions in an asymmetric way in G-quadruplex structures (Kim et al, 2003), and we found that TMS induces a rapid activation of PARP-1 and ␥H2AX, consistent with a DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of exogenous GSH has a similar effect to CsA and verapamil. Previous studies (56,57) have shown that PS translocation is independent of both nuclear activity (55) and caspase activation. It seems most likely that in HaCaT cells GSH efflux is involved in membrane rearrangement rather than caspase activation or DNA fragmentation in UVA-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%